Interfacing a laboratory approach using the microcomputer for instrumentation, data analysis, and control - Derenzo, Stephen E. (Prentice - Hall, 1990)
this text describes in practical terms how to use the Microcomputer to sense real - world quantities such as temperature, force, sound, light, etc,... to rapidly analyze the data, to display the results, or to use the results to perform a control function.